The Influence of the Jigsaw Learning Method Using Word Square Evaluation Media on the Understanding of Patient Safety in Nursing Students - Putri, Levya Afriliza Permana; Noor Hayati, Suci; Supriatin, Eva; Kusuma Putri, Tri Antika Rizki; Juniarni, Lia (STIKep PPNI Jawa Barat, 2025)
Background : Understanding patient safety is crucial for nursing students to prevent incidents and reduce adverse events during clinical practice. The jigsaw learning method combined with word square evaluation is an effective and interactive approach to enhance students' understanding, proving more beneficial than conventional teaching methods. Objective : This study aimed to assess the impact of the Jigsaw learning method with Word Square evaluation media on nursing students' understanding of patient safety. Method A quantitative study was conducted using a quasi-experimental design with a control group, pre-test, and post-test. The sample consisted of 40 Level I nursing students, selected through simple random sampling. Data were collected using a knowledge and understanding questionnaire. Results The intervention group, which received education using the Jigsaw learning method with Word Square evaluation media, showed significant improvement in understanding patient safety. Statistical analysis using the Wilcoxon signed-rank test indicated a significant difference (p = 0.000), and the Mann-Whitney test also confirmed a significant difference between the intervention and control groups (p = 0.000). Conclusion: The Jigsaw learning method with Word Square evaluation media significantly enhances nursing students' understanding of patient safety. This method can be implemented as an effective learning strategy at STIKep PPNI Jawa Barat.